Policy implementation of No Smoking area in Undata Public Hospital Palu City - Napirah, Muhammad Ryman; Suwendro, Novi Inriyanny; Hasanah, Hasanah (Preventif : Jurnal Kesehatan Masyarakat, 2020)
The determination of the No Smoking Area is an effort to protect the community against the risk of health problems due to the environment contaminated with cigarette smoke. The purpose of this study was to determine the implementation of the No Smoking Area policy at the Undata Regional General Hospital (RSUD), Palu, especially in the aspects of communication, resources, disposition. , and bureaucratic structures. This type of research is qualitative research with a case study approach. Determination of informants is done through purposive sampling technique, namely the researcher uses his judgment in selecting informants to obtain in-depth information according to the research objectives. the concept of communication is good enough. The KTR Task Force at Undata Hospital uses print and electronic media. In the resource variable, the results are not good enough. The KTR Task Force at Undata Hospital is still lacking in terms of the number, namely only 15 people previously numbered 30 people. The disposition variables obtained in this study are good enough. The appointment of the KTR task force at Undata Hospital is directly selected by the hospital director, but the supervisory officers still lack incentives. In the bureaucratic structure variable, the results were quite good. The most authorized person in implementing the implementation of the KTR policy implementation at the Undata Hospital Palu is the Task Force coordinator. The suggestion in this research is that the KTR Task Force at Undata Hospital should be added and the Undata Hospital should create a smoking area.